Conflict Management Style: Accounting for Cross-National Differences - Morris, Michael W.; Williams, Katherine Y.; Leung, Kwok; Larrick, Richard; Mendoza, M. Teresa; Bhatnagar, Deepti; Li, Jianfeng; Kondo, Mari; Luo, Jin-lian; Hu, Jun-chen (Journal of International Business Studies, 1998)
A problem in joint ventures between U.S. and Asian firms is that cultural differences impede the smooth resolution of conflicts between managers. In a survey of young managers in the U.S., China, Philippines, and India we find support for two hypotheses about cultural differences in conflict style and the cultural values that account for these differences: Chinese managers rely more on an avoiding style because of their relatively high value on conformity and tradition. U.S. managers rely more on a competing style because of their relatively high value on individual achievement.